2021
DOI: 10.1007/s12144-021-01905-2
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study to investigate male victims’ experiences of female-perpetrated domestic abuse in Jordan

Abstract: Battered husband syndrome has not been investigated in an Arab context, despite evidence of a significant increase in violence against men by women. This study investigated male victims' experiences of female-perpetrated domestic abuse in Jordan using a qualitative exploratory descriptive approach. Data were collected through semi-structured interviews with 33 married men from Amman and analyzed using interpretative phenomenological analysis. Five themes were identified: 1. causes of domestic abuse against men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…The Bedouin Arab cultures play central roles in shaping the Jordanian cultural and social context, and a patriarchal mentality permeates societal and religious influences, as well as legislation and state behavior (Garlick, 2020:6–7). Alsawalqa (2021b) indicated that clan and traditional thinking, societal structures, and norms lead men to divorce, or to stay in abusive relationships, and to perpetrate domestic abuse. Man Box beliefs trap men through pressures to adhere to socially constructed norms of masculinity and rigid notions of manhood, impeding men's formation of emotionally connected friendships and encouraging them to use violence against women, exhibit transgressive emotional behaviors, and promote male superiority (Heilman et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Bedouin Arab cultures play central roles in shaping the Jordanian cultural and social context, and a patriarchal mentality permeates societal and religious influences, as well as legislation and state behavior (Garlick, 2020:6–7). Alsawalqa (2021b) indicated that clan and traditional thinking, societal structures, and norms lead men to divorce, or to stay in abusive relationships, and to perpetrate domestic abuse. Man Box beliefs trap men through pressures to adhere to socially constructed norms of masculinity and rigid notions of manhood, impeding men's formation of emotionally connected friendships and encouraging them to use violence against women, exhibit transgressive emotional behaviors, and promote male superiority (Heilman et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Islamic religion and tribal culture play a role in shaping Jordanians' perceptions of sexuality. Conservative norms and the stereotype of masculinity in the socio-cultural Jordanian context have created cultural barriers that prevent men from expressing their emotions, perceiving themselves as victims of abuse, and reporting that they are victims of abuse by women, which is an unforgivable social stigma (Alsawalqa, 2021). Therefore, it is possible that participants were unable or unwilling to respond in a meaningful way to the Sexual Coercion subscale items (e.g., "My wife pressures me to have sex after an argument" and "My wife intentionally hurts me during sex") and the "Degradation" subscale items (e.g., "My wife has told me that I am sexually unattractive, " "My wife threatens me physically during arguments, " "My wife intentionally does things to scare me, " and "My wife threatens me physically during arguments"), which would have played a role in the accuracy of the response scores.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to address emotional abuse among men in marital relationships in Jordan. In a qualitative study, Alsawalqa ( 2021 ) found that Jordanian married men experienced psychological, emotional, and verbal abuse, coercive control, emotional neglect, and physical violence from their wives, and abusive wives used sex, children, isolation, and money as tactics to enable abuse. The major causes of abuse against the Jordanian husbands were wives' neglecting the children, house, appearance, and personal hygiene; wasting money; the wives' family interfering in the couple's private marital affairs; and the wife's betrayal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other family members may blame the victims for the violence or even feel ashamed of the situation. They may try to control them or even play down the abuse, doubting the credibility of the women's testimony [8][9][10].…”
Section: Introductionmentioning
confidence: 99%